GE_GERICHTE C/23440/2019 vom 24. August 2020 - GE Cour de justice (2020)
SÉQUESTRE(LP);ACTION EN DOMMAGES-INTÉRÊTS(SÉQUESTRE/LP);CESSION DE CRÉANCE(CO);PRINCIPE DE LA TRANSPARENCE(SOCIÉTÉ) | LP.271; LP.272; CNY.IV.ch1; CNY.V.leta.ch1; CNY.V.letb.ch2